Ability of Pre-school and Primary School Children to Assess the Quality of Explanations - Daugirdienė, Aušra; Brandišauskienė, Agnė; Endriuškienė, Danguolė (Pedagogika, 2016)
Explanations about the surrounding world are of particular significance for children since it is a way for them to learn and cognise the environment. However, Legare (2014) maintains that little is known about the impact of explanations on learning. For the past decade, explanations have been one of the major themes in the studies of cognitive psychology. They aim at answering the key questions: what is the nature of the phenomenon (explanation), what is it composed of, what are its quality criteria, how is it constructed and perceived by children (Lombrozo, 2006). Hence, the aim of the current paper is to explore the ability of pre-school and primary school children to assess the quality of explanations. The aforesaid aim was posed in accordance with the methodology developed by the authors (the methodology was designed with reference to the study of Baum, Danovitch, and Keil (Baum et al., 2008). The research involved 61 children: 20 pre-school children, and 41 primary school children (21 children of the second grade, and 20 children of the fourth grade respectively). The main conclusions of this research are: – children’s ability to assess the quality of explanations increases from pre-school age to the second grade of primary school, yet at this period, it remains unchanged (from the second to fourth grade); – despite that the ability to assess the quality of explanations on familiar and unfamiliar topics differs in both age groups (pre-school and primary school), the differences are not statistically significant. It has been determined that, assessing explanation on familiar and unfamiliar topics, pre-school children and fourth grade pupils are able to distinguish circular explanations on familiar topics in a more similar way than assessing explanations on unfamiliar topics. Moreover, older primary learners are more precise in assessing explanations on familiar rather than unfamiliar topics; – the oldest children (fourth grade learners) choose a noncircular explanation as a better one more knowingly and reasonably. Meanwhile, children of pre-school age and second grade pupils cannot often point out why they have chosen a noncircular explanation; – only older children (mostly fourth grade pupils and several second grade learners) are able to recognise and identify the structure of a circular explanation. The conducted research provides insights into the ability of small children to assess the acquired information. It is noteworthy that the assessment and creation of explanations is one of the mechanisms of learning and development (Bonawitz et al., 2008; Legare, & Lombrozo, 2014). Hence, their impact is obvious: explanations give a basis for learning, whereas prior knowledge is fundamental for explanations (Williams, & Lombrozo, 2013).